SAT0460 Low Bone Mass in Patients with Systemic Sclerosis: Relationships with Dickkopf-1 Levels and 25-Hydroxyvitamin D Status. (10th June 2014) - Seriolo, B.; Brizzolara, R.; Soldano, S.; Casabella, A.; Molfetta, L.; Paolino, S.; Cimmino, M.A.; Botticella, G.; Cutolo, M.
Abstract : Background: Patients (pts) affected by systemic sclerosis (SSc) show increased risk of bone loss as a result of the chronic inflammatory state, physical inactivity, gut malabsorption or malnutrition, decrease activation of vitamin D in the altered fibrotic skin 1 . Dickkopf-1 (Dkk-1) is recognized as a key regulator of bone remodeling by inhibition of the Wnt signalling required for new bone formation and is increased in postmenopausal pts. Objectives: In this study, bone mineral density (BMD), 25-hydroxyvitamin D [25(OH) D] status and Dkk-1 serum levels were evaluated in order to investigate in SSc pts a possible association between systemic osteoporosis and/or osteopenia, and Dkk-1 concentrations, based on different 25(OH) D status Methods: 64 postmenopausal pts (mean age 63±7 ys) affected by SSc (mean disease duration 6±3 ys) and 43 age-matched healthy controls (mean age 62±5 ys) were evaluated during their regular screenings and after informed consent in different periods of the year. Pts were not treated with vitamin D addiction or bone remodelling drugs. BMD (g/cm 2 ) of the lumbar spine (L1 -L4 ) and total hip was analyzed using dual-energy X-ray absorptiometry (DXA) scan (Lunar Prodigy, GE, USA). Dkk-1 serum levels were measured using an enzyme-linked immunosorbent assay and 25(OH)D3 serum levels were evaluated by radioimmunoassay. Vitamin D levels were classified as normal (>30 ng/ml), insufficient (<30 and >10 ng/ml), and deficient <10 ng/ml) Results: 47 of the SSc pts enrolled (73%) presented bone loss, in particular 24 pts (51%) showed osteoporosis and 23 osteopenia. BMD was found significantly lower in the SSc pts than in control group (lumbar spine: 0.990±0.192 g/cm 2 vs 1.039±0.18 g/cm 2 and total hip 0.809±0.125 g/cm 2 vs 0.903±0.11 g/cm 2, both p<0.001). Dkk-1 levels were significantly higher in SSc pts than in control group (2, 702±910 pg/mL vs 2, 164±662 pg/mL, p<0.007). Vitamin D levels were found lower in SSc patients than in controls (22.6+ 11 ng/ml vs 49.8+ 10 ng/ml). Interestingly, BMD at lumbar spine and Dkk-1 levels were found, respectively, significantly lower and higher in pts with deficient (n=14) and insufficient (n=30) vitamin D status when compared to pts with normal vitamin D status (lumbar spine 0.868±0.151 g/cm 2 vs 1.077±0.165 g/cm 2 ; total hip 0.662±0.266 g/cm 2 vs 0.788±0.121 g/cm 2, and Dkk-1 levels 3, 258±672 pg/mL and 3, 098+586 pg/ml vs 2, 033±697 pg/mL, respectively, all p<0.01). Conclusions: This study showed a significant increase in serum levels of Dkk-1, associated with osteopenia/osteoporosis in pts affected by SSc and deficient or insufficient vitamin D status, when compared to healthy postmenopausal subjects. Interestingly, since Dkk-1 blocks activation and proliferation of established myofibroblasts in vitro and blocks pericyte proliferation to PDGF, pericyte migration, gene activation, and cytoskeletal reorganization to TGF-β or connective tissue growth factor (all activated in SSc), its increase observed in SSc pts is matter of further investigations 2 . In addition, Dkk-1 should be considered a further marker of disease activity in SSc patients. References: Cutolo M et al. Autoimmun Rev 2011:12;84-7. Ren S et al. Proc Natl Acad Sci U S A.2013;110:1440-5. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4246